Mobility in the 21st Century: autonomous vehicles - Kauling, Lukas (2020)
Purpose and MethodologyThis study examines the social acceptance of Autonomous Vehicles (AVs) and the challenges surrounding it by (i) researching and analyzing the current statusof AVs, (ii) gathering the opinions of consumers by means of an online survey,as well as (iii) inter-viewing industry experts affiliated with firms involved in the development of AVs, and (iv) as-sessing the market ability of AVs through an evaluation of internal and external factors.Findings AVs are likely to be accepted by society, with the attendant loss of control of not only the vehicle itself, but also of the data that it generates.AVswill disrupt traditional car ownership, leading to the emergence of new business models in the sharing economy. AVsare the essential prerequisite for current shared mobility concepts to prevail, al though major challenges such as legal regulation andas yet unsolved liability issues can impede the market penetration of AVs.